Intensive Patient Monitoring Using LabVIEW - Rajendran, Manivasagam (Review of Computer Engineering Research, 2019)
In modern years, numerous telemedicine applications have been effectively implemented over wired communication technologies like POTS (Plain Old Telephone Systems) and ISDN (Integrated Service Digital Network). However, nowadays, modern wireless telecommunication means, such as the GSM (Global System for Mobile communication), GPRS (General Packet Radio Service), the forthcoming UMTS (Universal Mobile Telecommunication Systems) mobile telephony standards, and satellite communications, allow the operation of wireless telemedicine systems, freeing the medical personnel and/or the subject monitored from being bound to fixed locations . To offer a comparably dependable and easy way of monitoring for those people using newly available telecommunication technologies, we have proposed an Intensive Patient Monitoring System with database trailing ability. It will observe the results of simulation and its Hardware implementation can coincide up to its maximum accuracy. The investigational results prove the continuous monitoring of vital signs and be corroborate to be successful as per the required conditions. Intensive Monitoring System for various parameters monitoring with database tracking capability promises to be a powerful aid in monitoring multiple patients concurrently.